Reducing Dysmenorrhea using Accupressure on Teenage Girl at Pratama Clinic of Harapan Bersama Tegal - Ulfatul Latifah; Ratih Sakti Prastwi; Istiqomah Dwi Andari (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2020)
Most teenage girls experienced dysmenorrhea during their period (67.2%) and premenstrual syndrome (63.1%). Semarang District Health Office in 2013 reported as many as 50-80% of adolescents aged 12-19 years who experience dysmenorrhea overcome it pharmacologically and non-pharmacologically. Acupressure was one of non-pharmacology which could be an alternative for reducing dysmenorrhea. The aim of this study was to analyze the influence of acupressure in reducing dysmenorrhea. This study used a quasi-experiment with pre-test and post-test approaches. The respondent of this study was teenage girls with dysmenorrhea and obtained 23 respondent. First, respondents asked about their level of pain. Then respondents received 30 rounds acupressure at points Li 4 and Lr 3 for 3-5 minutes 3 times. Then re-evaluated the intensity of menstrual pains after the intervention finished. Data were analyzed using the Mann Whitney Test. The result of this study is that most of the respondents have mild pain levels (52.2%). After acupressure, complaints of pain decreased, where 47.8% did not feel pain. Based on statistical tests, the p-value of 0.001 obtained means that the provision of acupressure interventions has a significant effect on decreasing the level of dysmenorrhea in adolescent girls. The conclusion is that acupressure used as an alternative in treating dysmenorrhea.